ORGANISME PERUSAK KAYU PADA RUMAH RAKYAT DIYOGYAKARTA - Barly Barly; Nana Supriana; Agus Ismanto (Pusat Penelitian dan Pengembangan Hasil Hutan, 1986)
Many householders in Yogyakarta find that tney need to know something about wood destroying organisms. This may be because they suspect a problem exists in their house, or because they plan to buy or build new house, and wish to avoid serious problems during use. However, not all damage observed should cause concern, as some insects attact only green timber and their activity cease when the timber dries-up. On the other hand. some insects cause extensive and con- tinuing damage and can be difficult or expensive to control.